How to measure spiritual sensitivity at the IT user’s workplace? The construction process and method of validation of Spiritual Sensitivity Inventory (SSI) - Straś-Romanowska, Maria; Kowal, Jolanta; Kapała, Magdalena (Jak zmierzyć duchową wrażliwość pracowników IT w miejscu pracy? Proces konstrukcji i metody walidacji inwentarza wrażliwości duchowej (SSI), 2016)
This article outlines the creation of tools to measure spiritual sensitivity – Spiritual Sensitivity Inventory (SSI), starting from the assumptions underlying the source of its creation, through a phase of theoretical analysis of the construct used for development of an experimental method, a quantitative validation of the inventory, ending with a validation of quality, i.e. narrative interviews conducted in order to confirm the theoretical accuracy of the SSI. The authors clarify the construct of spiritual sensitivity, describe a deductive strategy for questionnaire creation, indicate the potential theoretical and methodological problems encountered by psychologists studying spirituality, present a spectrum of validation procedures and their ultimate effect – an accurate and reliable psychometric tool – the Spiritual Sensitivity Inventory. A developed spiritual sensitivity is beneficial not only in relationships between people but also in the educational, professional and social domain. In this light, an accurate and reliable diagnostic tool can be used in a business environment and organization
Ekonometria = Econometrics, 2016, Nr 2 (52), s. 53-76
Keywords: to measure spiritual sensitivity; questionnaire construction; questionnaire validation; validity and reliability of the questionnaire; Spiritual Sensitivity Inventory; IT users; model of ethical competencies aspects; płeć; wrażliwość duchowa; inwentarz; walidacja; trafność i rzetelność